Layered transition metal molecular magnets studied with implanted muons - Jestadt, T; Kurmoo, M; Blundell, S; Lovett, B; Pratt, F; Hayes, W (Elsevier, 1999)
We have carried out magnetic measurements on the layered magnets Ni-2(OH)(3)(N(CN)(2)) (NiAM), Co-5 (OH)(8)(N(CN)(2))(2). 6H(2)O (CoAM), Co-5(OH)(8) (C12H25SO4)(2). 2NH(3) (CoDOS), and Co-5 (OH)(8) (C7H15CO2)(2). 4H(2)O ( CoCAP), using various experimental methods, including muon spin relaxation (mu SR). We find phase transitions at temperatures T-M in all the samples, characterized by a change in the magnetic susceptibilty and loss of initial muon spin polarization.